Lifestyles associated with sedentary lifestyles in the community Quebrada “La Paja”, Ecuador - Carranza, Jelitza N.; Ganchozo, Allison M.; Hidalgo, Kristel J.; Morán, Sthela P.; Fernández, Yumy E.; Cedeño, Wilmer B. (Revista Gregoriana de Ciencias de la Salud, 2025)
A sedentary lifestyle, defined as the practice of physical activity for less than 15 minutes and less than three times per week, is a modifiable factor in chronic noncommunicable diseases. This study aimed to analyze the lifestyles associated with sedentary lifestyles in the Quebrada “La Paja” community in Portoviejo. A non-experimental, cross-sectional, exploratory, and descriptive study was conducted with 103 people from 24 families. The results indicated that most of the population leads a sedentary lifestyle, with low consumption of fruits and vegetables. In addition, a sedentary lifestyle was related to specific occupations and low educational levels; 29.17% of the participants did not perform any physical activity. It was concluded that work occupation, low educational level, and unhealthy eating habits are key factors in sedentary lifestyles.